Quality assurance in contemporary clinical laboratories - Figueroa-Montes, Luis (2023)
This review encompasses how technological and management advances should be articulated in quality assurance, to guarantee the best analytical performance of laboratory tests for the benefit of decision making in the diagnosis, treatment and monitoring of diseases or for prevention programs in healthy populations. All this focused on contemporary clinical laboratorios. We will address topics such as: big data and artificial intelligence, complex methodologies, precision medicine, laboratory demand management, point-of-care testing, and Laboratory Medicine advocacy; and recommendations are made to articulate these trends with clinical laboratories.